2021
DOI: 10.3389/fmed.2021.625787
|View full text |Cite
|
Sign up to set email alerts
|

HIV Stigma and Discrimination: Perspectives and Personal Experiences of Healthcare Providers in Yogyakarta and Belu, Indonesia

Abstract: Stigma and discrimination are major challenges facing People Living with HIV/AIDS (PLWHA) globally due to their HIV status. As part of a larger qualitative study in Yogyakarta and Belu, Indonesia, using in-depth interviews with 92 PLWHA (52 women, 40 men) and 20 healthcare providers, this paper describes perspectives and personal experiences of the 20 healthcare providers, relating to HIV stigma and discrimination toward PLWHA in both study settings. The healthcare providers were recruited from healthcare faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 38 publications
10
66
0
1
Order By: Relevance
“…In line with the concepts in the HIV stigma framework and the reports of previous studies in other settings [3,17,[19][20][21][22]52], the current study confirms that HIV stigma and discrimination also experienced by participants within communities where they lived and worked. These manifested in a range of unfair treatments by other community members, such as refusal of eating food they have touched, avoidance of shaking hands or sitting next to them and keeping a distance from them due to the fear of contracting HIV which seemed to be supported by a lack knowledge of the means of HIV transmission [13,14,[25][26][27]52]. This study also provides new evidence that discriminatory and stigmatizing attitudes and behaviors of neighbors and friends or community members towards the participants were influenced by negative social and moral perceptions or judgements about HIV and PLHIV, which seemed to be rooted in their religious thoughts about extra-marital sex and sex with multiple sex partners as sins and HIV infection as a curse for PLHIV.…”
Section: Discussionsupporting
confidence: 89%
“…In line with the concepts in the HIV stigma framework and the reports of previous studies in other settings [3,17,[19][20][21][22]52], the current study confirms that HIV stigma and discrimination also experienced by participants within communities where they lived and worked. These manifested in a range of unfair treatments by other community members, such as refusal of eating food they have touched, avoidance of shaking hands or sitting next to them and keeping a distance from them due to the fear of contracting HIV which seemed to be supported by a lack knowledge of the means of HIV transmission [13,14,[25][26][27]52]. This study also provides new evidence that discriminatory and stigmatizing attitudes and behaviors of neighbors and friends or community members towards the participants were influenced by negative social and moral perceptions or judgements about HIV and PLHIV, which seemed to be rooted in their religious thoughts about extra-marital sex and sex with multiple sex partners as sins and HIV infection as a curse for PLHIV.…”
Section: Discussionsupporting
confidence: 89%
“…The use of such thinking as a parameter to assess the behavior of PLWHA causes the reluctance of health-care providers to serve, interact, and feel disgusted with HIV patients [21]. This supports the findings of a previous study which reported that the inclusion of personal religious beliefs in the provision of health to PLWHA led to clashes between personal religious values and professional expectations [20].…”
Section: Religioussupporting
confidence: 77%
“…In the learning process, all nurses and midwives are equipped with knowledge and skills according to professional competencies/ standards, especially in providing services to PLWHA. However, the reality is that after they graduate and get a diploma, they are not automatically able to enter the ministry [18], [20].…”
Section: Level Of Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Reasons for HCPs' stigmatization and discrimination against PLHIV include insufficient knowledge of HIV, perceived occupational risk of infection, and fear of death. 15 Other factors that might play a role in HCPs' attitudes include unfamiliarity with universal precautions and lack of adequate protective equipment. 7,13,16 Providers' discrimination against PLHIV has also been attributed to the behaviors believed to have led to infection, such as homosexuality, having multiple sexual partners, and injecting drugs.…”
Section: Introductionmentioning
confidence: 99%